Voir les fantômes. Sentir la multiplicité temporelle de la ville grâce aux œuvres d’art - Estelle Grandbois-Bernard (Conserveries Mémorielles)
Our cities are populated of multiple time frames, inhabited by memories, dreams and expectations of the individuals who make them live and buildings that shape them. Looking through them, we can sometimes meet some ghosts, fleeting appearances of the past even in the present, which take the form of ruins, architectural differences, and other traces of the disappeared, and allow to feel the presence of absence, the intermingling of time to clean the urban reality. This article proposes to focus on how artists invest the time multiplicity of present to highlight and visually translate, and perhaps turn our attention to our living space. Through the study of temporal experiences shaped by three contemporary works of art about the transformation in cities (Souvenirs de Berlin-Est by Sophie Calle, The Writing on the Wall by Shimon Attie and Phantom Shangai by Greg Girard), I try to think about how they let fell the presence of the past in urban space, and how they all seem to suggest that “living together” also mean “living with our ghosts”.